Reviving catalytic activity of nitrides by the doping of the inert surface layer to promote polysulfide conversion in lithium-sulfur batteries. (June 2019) - Hao, Boyu; Li, Huan; Lv, Wei; Zhang, Yunbo; Niu, Shuzhang; Qi, Qi; Xiao, Shujie; Li, Jia; Kang, Feiyu; Yang, Quan-Hong
Abstract: Lithium-sulfur batteries show great promise among future battery technologies, but their cycle life is mainly restricted by the shuttling effect of soluble lithium polysulfides (LiPSs). The catalytic conversion of LiPSs appears to be a fundamental way of suppressing this. The highly conductive metal nitrides show great potentials as high-performance catalysts, but the presence of a thin surface oxidation layer, which is normal for nanomaterials, restrains the surface electron transfer and catalytic activity. In this study, we demonstrate that the doping of the oxidation layer is an ideal solution to reviving and enhancing the catalytic activity of nitrides. As a proof of concept, sulfur-doping of a titanium nitride (TiN) oxidation layer is presented here, and the TiS bonds formed are responsible for transmitting electrons from the conductive TiN matrix thus guaranteeing a high catalytic activity. Interfacing of TiS with TiO bonds at the atomic level helps realize strong trapping and fast conversion of LiPSs simultaneously. As a result, the specific capacity, rate performance, and cyclic stability are all greatly improved by the interlayer composed of sulfur-doped TiN and graphenes, which indicates a practical avenue for building high performance lithium-sulfur batteries. Graphical abstract: Image 1 Highlights: Sulfur doping of inert surface layer revives catalysis of TiN towards polysulfides. TiS interfacing with TiO bonds results in fast conversion of polysulfide. Using sulfur-doped TiN in the interlayer prolongs the cycling life of LiS batteries.